Understanding Push Notification Fatigue: User Tolerance and Management Behavior in Mobile Applications - Thanaporn Srisawat; Somchai Wongsuwan; Siriporn Chaiyaporn (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Push notifications are widely used by mobile applications to deliver timely information and maintain user engagement. However, excessive, repetitive, irrelevant, or poorly timed notifications may contribute to interruption, cognitive burden, emotional irritation, and notification fatigue. This proposed study examines push notification fatigue, user tolerance, and notification management behavior among mobile application users in Thailand. Using a cross-sectional survey design, the study will collect data from approximately 280 Android and iOS smartphone users who receive push notifications daily. The study integrates daily notification frequency, perceived notification load, notification relevance, timing appropriateness, actionability, perceived user control, notification fatigue, user tolerance, and management behavior. Respondents will be grouped into light-, medium-, and heavy-notification-load users based on their reported daily notification frequency. Quantitative data will be analyzed using descriptive statistics, reliability testing, group comparison tests, correlation analysis, and multiple regression. Open-ended responses will be analyzed through thematic content analysis to identify characteristics of useful and intrusive notifications. The study is expected to contribute to the literature by treating notification fatigue as a distinct user experience rather than a general extension of smartphone overuse, social media fatigue, or technostress. Practically, the study may inform more user-centered notification design by emphasizing relevance, appropriate timing, actionability, proportional urgency, privacy protection, and meaningful user control.